ESG research unveiled: publication patterns, dominant themes, and future avenues – a bibliometric approach - Anisha Mishra; Mohammed H. Alsamhi; Mohammed Bajaher; Waleed M. Alahdal (Cogent Business & Management, 2025)
This study examines how research on Environmental, Social, and Governance (ESG) topics has developed over time, and the key themes that researchers have focused on. Using data from the Scopus database, we analyzed 884 ESG-related studies published between 2008 and 2024 in top academic journals. We applied various bibliometric techniques, such as author citation analysis, co-citation analysis, bibliometric coupling, and keyword mapping, to identify major research trends in ESG. Our analysis, conducted using VOSviewer and Biblioshiny (R Studio), found five main research themes: ESG & Corporate Accountability, ESG Investing & Sustainable Finance, ESG Risks & Financial Stability, ESG & Sustainable Development Goals (SDGs), and ESG-driven Business Transformation & Innovation. This study also highlights a growing interest in ESG, with an increasing number of publications and citations over time. Unlike previous studies that focused only on citations, this research combines multiple analytical methods to provide a more complete picture of the ESG literature. These findings offer useful insights for businesses, policymakers, and investors. By understanding ESG trends, companies can improve sustainability-focused decision making, manage risks better, and enhance financial performance. This study also helps organizations align their ESG strategies with regulations, investor expectations, and long-term business goals.